Reduced sensitivity to thyroid hormones is associated with differentiated thyroid cancer in the euthyroid thyroidectomy population - Xu, Huaijin; Liu, Hongzhou; Hu, Xiaodong; Jia, Xiaomeng; Xue, Zhe; Wang, Anning; Kang, Shaoyang; Lyu, Zhaohui (Frontiers in Endocrinology, 2025)
BackgroundThe inconclusive associations between thyroid-related hormones and differentiated thyroid cancer (DTC) suggest complex pathophysiologic processes, for which thyroid hormone sensitivity may provide new insights.MethodsWe retrospectively analyzed preoperative clinical data and postoperative pathological data of 9,515 euthyroid adults who underwent thyroidectomy for thyroid nodules pathologically confirmed as benign nodules or DTC. Composite thyroid parameters were calculated, including TSH index (TSHI), thyrotroph thyroxine resistance index (TT4RI), FT3/FT4 ratio (FT3/FT4) and the thyroid’s secretory capacity (SPINA-GT).ResultsIncreased TSHI (OR=1.34, 95%CI: 1.27-1.41) and TT4RI (OR=1.35, 95%CI: 1.28-1.42) reflecting reduced central thyroid hormone sensitivity, decreased FT3/FT4 (OR=0.81, 95%CI: 0.77-0.86) reflecting reduced peripheral thyroid hormone sensitivity, and decreased SPINA-GT (OR=0.78, 95%CI: 0.74-0.82) were associated with DTC after adjustment for confounders. The contributions of thyroid hormone sensitivity indices remained in subgroups stratified by age, sex, metabolic factors, thyroid autoimmunity status, and nodule size. A non-linear relationship between thyroid hormone sensitivity indices and probability of DTC was observed. The association of DTC with TT4RI or TSHI was stronger than with other thyroid parameters such as TSH (thyroid stimulating hormone). ROC analysis for the distinction between DTC and benign disease showed no single thyroid parameter with the coexistence of high sensitivity and specificity.ConclusionReduced central and peripheral sensitivity to thyroid hormones is associated with DTC in the euthyroid thyroidectomy population and provides additional information on the odds of malignancy in thyroid nodules at risk for surgery, warranting consideration of the role of sensitivity to thyroid hormones in mechanisms and prediction models for DTC.